INDEPENDENCE OF THE PROSECUTOR'S OFFICE REGARDING PROSECUTORIAL DISCRETIONARY IN REALIZING RESTORATIVE JUSTICE (CASE STUDY IN NORTH MALUKU HIGH PROSECUTOR'S OFFICE) - Faissal Malik; Muhammad Amin Hanafi; Nurlaila Kadarwati Papuluwa; Arief Budiono (RADJA PUBLIKA, 2025)
The urgency of this research necessitates prosecutors to implement restorative justice to minor crimes through the principle of dominus litis. It must be subject to clear limitations and parameters in the ius constituendum. The restorative justice approach aims to restore the condition of the victim, the perpetrator, and the community. The objective of this research is to achieve prosecutorial discretion through restorative justice. The research method used is empirical law. The data types used are primary data (primary, secondary, and tertiary legal materials) and secondary data (literature studies and interviews). The North Maluku High Prosecutor's Office prioritizes restorative efforts in cases of assault. This mechanism involves the victim's family and the perpetrator's family. The number of cases in the jurisdiction of the High Prosecutor's Office in 2024 was 47 cases and 14 of them were resolved using restorative justice. This is in line with the provisions of Article 34A of Law Number 11 of 2021 concerning the Prosecutor's Office, which states that the principle of discretion regulated in Article 139 of Law Number 8 of 1981 concerning Criminal Procedure Law is carried out without ignoring the principle of law enforcement objectives which include achieving legal certainty, a sense of justice, and its benefits in accordance with the principles of restorative justice.